Analysis of growth and wilting point of chili (Capsicum annum L.) seedlings using three types of planting media - Wahyuni, Ida; Fathoni, Ahmad; Suhairin, Suhairin; Suriadi, Ahmad; Gunawan, Adi; Basirun, Basirun (Jurnal Agrotek Ummat, 2024)
Cayenne pepper plants are one of the plants that are susceptible to excess and lack of water during their growth period. Lack of water can cause chili seeds to not grow optimally, so chili plant nurseries need ideal media to be able to provide optimal water. This research aims to determine the growth and duration of the permanent wilting point in the growth of chili plant seeds based on differences in planting media in the form of magot compost, soil containing pumice and paddy soil under conditions without watering. The treatment in this research used three different planting media, namely compost, pumice, and paddy soil media. Providing water to chili plants by watering 3 times a day and without watering. The research method uses experimental methods with observations in the greenhouse and there are three treatments, namely using magot compost, pumice and soil media. The parameters observed included growth in height, number of leaves, and width of the plant leaves as well as the length of time to the permanent wilting point. The data from the research were analyzed using ANOVA with the help of SPSS. The results of the research showed that the compost media had the best growth with a height of 9 cm, the number of leaves was 6 pieces, and leaf width 2.9 cm, while the permanent wilting point duration of the three media used was found in compost media, which experienced the longest permanent wilting point at the age of 10 days. So it can be concluded that the best planting medium is found in maggot compost media with the highest growth and longest wilting point.